A DESIGN OF TWISTED DOUBLE CHANNEL SCISSORS FOR OPTICAL FILTER - H. M. Hairi; T. Saktioto; Dedi Irawan; J. Ali (Komunikasi Fisika Indonesia, 2014)
Microring resonators have emerged in the past few years in integrated optics and have been used extensively in many fields due to its advantages. The response from coupled ring resonators can be custom designed by the use of different coupling configurations [1]. In certain cases, ring resonators can be used as wavelength filter when the wavelength fits a whole multiple times in the circumference of the ring [5,6]. In this paper, we compare and contrast the effect of light propagation/ power distribution characteristics associated with ring configurations. We have limited our study to side-coupled integrated space sequence of resonators or as known as SCISSORs using OptiFDTD Photonics Simulation Software V8.0.